Relationship between Oil Price, Inflation, and Economic Growth in BRICS Countries: Panel Cointegration Analysis - Aidarova, Aina B.; Ramashova, Aissulu Nurmambekovna; Baisholanova, Karlygash; Jaxybekova, Galiya; Imanbayev, Aliy; Kenzhebekova, Indira; Kelesbayev, Dinmukhamed (International Journal of Energy Economics and Policy, 2024)
In 2001, Jim O’Neil coined the term “BRIC” to refer to the economies of Brazil, Russia, India and China. In 2011, South Africa joined the group, and it was updated to “BRICS”. These countries have a significant impact on the world economy, and there are numerous studies examining their macroeconomic structures. This study focuses on the relationship between economic growth, oil revenues, and inflation levels in BRICS countries from 2000 to 2021 and uses panel cointegration analysis. Many studies showed a relationship between these variables in different countries and unions. This study aims to determine if these relationships hold for BRICS countries. The results suggest a cointegration relation and a causality relation between economic growth, inflation, and oil revenues in BRICS countries. This finding demonstrates the impact of energy, specifically oil revenues, on economic growth. However, other macro indicators also affect economic growth, as suggested by existing literature. Therefore, future studies could improve on this research by including additional social and economic variables to evaluate the impact of oil revenues on economic growth from multiple perspectives.